Psychotropic Management in Cotard Syndrome: Case Reports Supporting Dual Medication Management - Adam J. Fusick; Chemar Davis; Steven Gunther; Cory Klippel; Gregory Sullivan (Case Reports in Psychiatry)
Cotard syndrome is a rare presentation where patients present with nihilistic thoughts of dying or already being dead. These delusions manifest from either a medical or psychiatric etiology and can be difficult to treat. Recently Couto and Gonçalves purposed that treatment should include an atypical antipsychotic alone or in combination with either a mood stabilizer or antidepressant. Here the authors advocate for a more specific but well-known psychotropic regimen, namely the combination of olanzapine and fluoxetine. We conducted a literature review and of 246 papers identified, only three reported using a combination of fluoxetine and olanzapine with many of them having limited or confounding information that make it difficult for us to comment on the historically efficacy of this medication combination. Therefore, the authors provide two case examples of patients being treated successfully with olanzapine and fluoxetine. One, a 66-year-old male veteran and another 76-year-old male veteran. Both of these cases hold significance as the patient’s psychotic depression was so severe as to warrant ECT as a possible treatment. In both cases, this medication combination was able to avoid the procedure. Overall, with the addition of our cases and the sparse information available in the literature, we propose the combination of fluoxetine and olanzapine as an effective Cotard syndrome treatment.